Primary structure of the ompF gene that codes for a major outer membrane protein of Escherichia coli K-12. - Inokuchi, K (1982)
The nucleotide sequence of the ompF gene coding for a major outer membrane protein of Escherichia coli K-12 has been determined and the amino acid sequence of the OmpF protein was deduced from it. The OmpF protein contains 340 amino acid residues, and is produced from a precursor having 22 extra amino acid residues, the signal peptide, at the amino terminus. The expected secondary structure of the OmpF protein had a high beta-sheet content with a low alpha-helix content. The promoter region and the transcription termination region of the ompF gene had a significantly high AT content, while the AT content of the coding region was about the same as the average AT content of the E. coli chromosome. Following the termination codon, a typical rho-independent transcription termination signal was observed. The codon usage in the ompF gene was highly nonrandom; the codons preferably utilized are those recognized by the most abundant species of isoaccepting tRNAs or those, among synonymous codons recognized by the same tRNA, that can interact more properly with the anticodon.